Voluntarily and involuntarily childless married women: Problems, feelings, and coping - Crisostomo, Janina Paula C. (Animo Repository, 1999)
This paper deals with the problems, feelings and coping strategies of the voluntarily and involuntarily childless women. This is a descriptive study in nature that identifies the problems, feelings and coping strategies of childless married women across their length of childlessness and state of being childlessness. The method used was a structured in-depth interview, which consisted questions pertaining to problems, feelings and coping strategies. The data was analyzed qualitatively and was categorized into voluntary childlessness for short duration, voluntary childless for long duration, involuntary childlessness for short duration, and involuntary childlessness for long duration. Results showed that there are similarities and differences in the problems, feelings and coping strategies of both the voluntary and involuntary childless women, whether their childlessness was for short or long duration. Some of the problems encountered were pressures from the family, friends, and relatives and from jobs. Most of the respondents were happy and contented with their lives. There are some respondents that responded that they do not have problems towards their situation. All the respondents were able to cope with their situation positively. They have accepted their situation and were satisfied with their lives.